Predictors of rice output among selected irrigated rice fields in Sta. Fe, Leyte. - Pedrosa, Jose Idore (Tacloban City Jose Idore Pedrosa, Mark Dave Natividad Lebria [and] Miamor Dagot Natividad, 2010)
Rice output is measured in this paper as the average yield or the number of cavans produced per cropping season. This variable is used as the dependent variable in the production function represented by Qy. This paper examines the predictors affecting rice output among selected irrigated rice fields in seven barangays of Sta. Fe, Leyte. This paper also aimed to identify common problems encountered and the solutions proposed by the respondents. An interview schedule which took into consideration the demographic profile and socio-economic characteristics of the farmers as well as the cost of direct inputs was administered to 117 selected farmers which represent 30% of the total farmers in each barangay. Regression runs were made and Model 2 was chosen to predict rice output per cropping season. It was found out that the predictors affecting rice production (at alpha=.05) are irrigation, quantity of seeds used, the cost of pesticide, carabao use and land master use. It was also found out that the main problem that farmers encounter is the lack of financial resources. Based on the findings of the study, the researchers recommend that the government should provide and maintain effective irrigation facilities and establish rice production credit and insurance programs to rice farmers.
Undergraduate thesis (B.A.S.S. Economics)--University of the Philippines, Tacloban
Keywords: Social Science